PENGARUH KEDALAMAN MUKA AIR TANAH DAN MULSA ORGANIK TERHADAP EMISI CO2 PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI LAHAN GAMBUT - Pernando Nababan; Wawan '; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the effect of water level and organic mulch on CO2 emissions of oil palm in peatland. Research was conducted at the oil palm plantation of ​​PT. Teguh Karsa Wana Lestari (TKWL) in Buantan Besar village, Bungaraya, Siak District, from October 2014 to February 2015. This research used Split Plot Design, consist of 2 factors. The first factor is the groundwater surface depth as main plot, were: water level depth 50 cm, 70 cm dan 90 cm. The second factor is application organic mulch as sub plot, were: without giving organic mulch, giving palm oil empty fruit bunch (POEFB), palm frond and Mucuna bracteata. Therefore obtained 12 combinations of treatments and 3 replications, so obtained 36 units experiment. Parameters observed were the CO2 emmisions, soil temperature and soil water content. Data were analyzed using Analysis of Variance (ANOVA). The data obtained were further tested by Least Significant Diference (LSD) at 5 % level. Based on the result it can be concluded that is not significantly effect on CO2 emissions. The water level and organic mulch affected on soil temperature and soil water content. The results of linear correlation analysis showed the depth of groundwater surface factors, organic mulch and soil temperature affected CO2 emissions rate. Soil water content was not significantly affect on CO2 emissions rate, it shows by the low of correlation coefficient (r). Keywords : CO2 emissions, water level, organic mulch